Cervical range of motion and patient-reported outcomes in patients undergoing surgical treatment for degenerative pathology of the subaxial cervical spine (C3–C7) - Claudio Cornali; Claudia Riva; Francesco Belotti; Emma Sala; Marco Mazzali; Nicola Pagani; Simona Serioli; Riccardo Bergomi; Marco Maria Fontanella; Luca Zanin (Neurological Sciences, 2026)
Abstract Background Degenerative subaxial cervical (C3–C7) disease often requires surgery when conservative care fails, yet the relationship between post-operative cervical range of motion (ROM) and patient-reported outcomes is poorly defined. We evaluated post-operative ROM and its cross-sectional association with clinical outcomes. Methods In a retrospective cohort with cross-sectional outcome assessment, 100 patients operated between 2015 and 2021 (anterior or posterior approach, with or without instrumentation) were assessed at a single follow-up visit. Neck-specific disability (Neck Disability Index, NDI), health-related quality of life (Short Form-12, SF-12) and cervical ROM (CROM device) were measured; pre-operative ROM was unavailable. Spearman and partial Spearman correlations (adjusted for age and comorbidity) and Mann–Whitney U comparisons were used. Results Median NDI was 16% (IQR 8–35), in the minimal-disability band; the SF-12 physical component (PCS-12, 40.2 ± 10.0) was below and the mental component (MCS-12, 47.6 ± 11.1) near the population norm of 50. NDI correlated negatively with ROM in all planes and with total ROM (ρ = −0.46, p < 0.001), and PCS-12 positively (axial rotation ρ = +0.52, p < 0.001); MCS-12 showed no significant association. Associations persisted after adjustment and in a Pearson sensitivity analysis. Exploratory comparisons, confounded by case-mix, showed greater axial rotation after the anterior approach. Conclusions Greater post-operative ROM is associated with lower neck-specific disability and better physical quality of life, independent of age and comorbidity, but not with mental quality of life. The cross-sectional design precludes inference about the direction of these associations. Prospective studies with pre-operative ROM baselines are needed.